Kabzanie Vincenza - Pełczyński, Grzegorz (Tematy i Konteksty, 2018)
Stanisław Vincenz (1888–1971) is famous Polish writer. His bigges twork is novel Na wysokiej połoninie. It is about different cultures onsouth-east old Poland. There were different ethnic groups on this land.Article says about Armenians in Vincenz’s work.